2020
DOI: 10.1111/ecc.13310
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting knowledge levels of oncology nurses about skin cancer and sun protection

Abstract: Over the past decades, the incidence of melanoma and non-melanoma skin cancers has been increasing worldwide (Lin, Eder, & Weinmann, 2011). Many factors affect an individuals' knowledge and behaviour regarding skin cancer and sun protection (Çelik, Ilçe,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Similarly, a study conducted in Turkey examined the performance of female oncology nurses on the Skin Cancer and Sun Knowledge (SCSK) scale. The study found that nurses who were above 40 years of age and had received education on skin cancer demonstrated better performance on the scale [ 32 ]. However, older patients of our study had significantly lower odds of good knowledge about skin cancer, which is in line with the findings of another study in Iran showing low skin cancer knowledge among the elderly [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a study conducted in Turkey examined the performance of female oncology nurses on the Skin Cancer and Sun Knowledge (SCSK) scale. The study found that nurses who were above 40 years of age and had received education on skin cancer demonstrated better performance on the scale [ 32 ]. However, older patients of our study had significantly lower odds of good knowledge about skin cancer, which is in line with the findings of another study in Iran showing low skin cancer knowledge among the elderly [ 33 ].…”
Section: Resultsmentioning
confidence: 99%